Graphene oxide membranes with high permeability and selectivity for dehumidification of air. (September 2016) - Shin, Yongsoon; Liu, Wei; Schwenzer, Birgit; Manandhar, Sandeep; Chase-Woods, Dylan; Engelhard, Mark H.; Devanathan, Ram; Fifield, Leonard S.; Bennett, Wendy D.; Ginovska, Bojana; Gotthold, David W.
Abstract: Hierarchically stacked 2D graphene oxide (GO) membranes are a fascinating and promising new class of materials with the potential for radically improved water vapor/gas separation with excellent selectivity and high permeability. This paper details dehumidification results from flowing gas mixtures through free-standing GO membrane samples prepared by a casting method. The first demonstrated use of free-standing GO membranes for water vapor separation reveals outstanding water vapor permeability and H2 O/N2 selectivity. Free-standing GO membranes exhibit extremely high water vapor permeability of 1.82 × 10 5 Barrer and a water vapor permeance of 1.01 × 10 −5  mol/m 2 sPa, while the nitrogen permeability was below the system's detection limit, yielding a selectivity >10 4 in 80% relative humidity (RH) air at 30.8 °C. The results show great potential for a range of energy conversion and environmental applications.